The determinants of open interest in option markets. Issue 2 (25th October 2021) - Harris, Jeffrey H.; Shafer, Michael
Abstract: Open interest, the supply of options created, is driven by proxies for asymmetric information and theta (since option writers benefit from theta). Open interest increases with the magnitude of stock return momentum, especially for short‐sale constrained equities with negative return momentum. Moreover, open interest is positively related to firm risk (i.e., option writers respond to hedging demand), but the elasticity of supply decreases toward expiration when adverse selection costs become more salient. Open interest is also informative—we document that increases in open interest significantly presage seasoned equity offerings (SEOs), reflecting informed trading that is not evident with volume metrics.